2012
DOI: 10.1007/s00345-012-0835-z
|View full text |Cite
|
Sign up to set email alerts
|

Poor early graft function impairs long-term outcome in living donor kidney transplantation

Abstract: BackgroundPoor early graft function (EGF) after living donor kidney transplantation (LDKT) has been found to decrease rejection-free graft survival rates. However, its influence on long-term graft survival remains inconclusive.MethodsData were collected on 472 adult LDKTs performed between July 1996 and February 2010. Poor EGF was defined as the occurrence of delayed or slow graft function. Slow function was defined as serum creatinine above 3.0 mg/dL at postoperative day 5 without dialysis.ResultsThe incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 14 publications
2
34
0
Order By: Relevance
“…Furthermore, the long-term graft survival rates have been shown to be significantly lower compared to those patients with immediate graft function. Hellegering et al [5] showed that BMI, pre-transplant dialysis and warm ischemia time are associated with slow graft function on a multivariate analysis, and therefore, a meticulous selection of the donors and a short warm ischemia time should always be attempted. Following this direction, there have been multiple studies addressing the prevention of ischemia and posterior reperfusion injury in living donor nephrectomy.…”
mentioning
confidence: 99%
“…Furthermore, the long-term graft survival rates have been shown to be significantly lower compared to those patients with immediate graft function. Hellegering et al [5] showed that BMI, pre-transplant dialysis and warm ischemia time are associated with slow graft function on a multivariate analysis, and therefore, a meticulous selection of the donors and a short warm ischemia time should always be attempted. Following this direction, there have been multiple studies addressing the prevention of ischemia and posterior reperfusion injury in living donor nephrectomy.…”
mentioning
confidence: 99%
“…Recurrent disease will appear in the chronic setting, rather than acute rejection [54,55]. Recurrence of both focal glomerulosclerosis and membranoproliferative glomerulonephritis is more frequent in the pediatric population [56].…”
Section: Resultsmentioning
confidence: 99%
“…The rate of resumption of graft function does not affect long-term survival as much as a delay in function. 8 In a retrospective study of graft survival that excluded patient deaths (n = 472 transplant recipients), Hellegering and associates 23 reported that the difference in death-censored survival rates between patients with DGF and normal graft function resulted in an adjusted hazard ratio of 6 24 Understanding the reason for the persistently close relation between graft survival and DGF warrants further study and a need to formulate further modalities for the optimal treatment of DGF after transplant.…”
Section: Effects Of Delayed Graft Function On Outcomes Of Living-donomentioning
confidence: 99%